Therapeutic intervention with horses vision from the psychology - Morey Yrigoyen, Fernanda (2014)
Assisted therapeutic intervention with horses is a comprehensive tool, as well as different forms of application of psychology. Is intended for multiple diseases in which the use is permitted as co equine therapist.A brief description of the therapy classes, functions and conditions and ways of working that Equinoterapeuta and his team must have to fully perform is done.It describes the conditions of the most important element of therapy is the horse, its characteristics and conditions of use, in particular, personal observation and methodical in the last decade of professional activity.